Exploration of Seasonal Dynamics of Tropical Indo-Pacific Ocean during Dry, Wet and Neutral Years in Indonesia using Composite Method - Ariska, Melly; Suhanda, Alfin; Suhadi, Suhadi; Supari, Supari; Irfan, Muhammad; Iskandar, Iskhaq (Universitas Negeri Surabaya, 2024)
Applying rainfall data for each month from Princeton University from January 1948 to December 2016, the impact of the Pacific El Niño-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD), which is focused in the Indian Ocean, on rainfall in Indonesia was examined. IOD occurrences are significantly correlated with rainfall, as seen by the simultaneous association of seasonal rainfall anomalies during the peak of the rainy season (NDJ) in Indonesia's dry, wet, and neutral years, as well as other climatic indices in both climates. Rainfall has occurred in parts of South Sumatra, Java, South Kalimantan, Nusa Tenggara, Sulawesi, and East Papua. Meanwhile, ENSO events significantly correlate with rainfall in the southern regions of Sumatra, Java, Kalimantan, Sulawesi, and Papua. El Niño is associated with low sea surface temperature anomalies in the Indonesian Sea and southeast Indian Ocean. The low SST anomaly lowers the mean sea surface level (MSL). It reduces the amount of water vapor in the atmosphere, suppressing atmospheric convection in Indonesia and leading to a very sharp decrease in rainfall. Based on the forecasting and exploration of rainfall patterns in Indonesia described in this study, this research can be used as a reference for the government to prepare preventive measures against extreme global climate change events and to predict hydrometeorological disasters in disaster-prone areas.